Review of the Safety and Feasibility of Rapid Infusion of Rituximab - Atmar, Jill (American Society of Clinical Oncology, 2010)
Added to standard chemotherapy, rituximab improved survival in patients with non-Hodgkin's lymphoma; added to fludarabine-based regimens, it improved response and survival in patients with chronic B-cell lymphocytic leukemia.